Some Things Can Never Be Unseen: The Role of Context in Psychological Injury at War - de Rond, Mark; Lok, Jaco (Academy of Management Journal, 2016)
Recent wars in Iraq and Afghanistan have reignited debates on how to prevent and manage psychological injury among returning troops. These debates point to the psychological cost of war as a grand challenge whose scale and complexity stretch far beyond the already large and growing number of veterans affected. We use a unique ethnography of a military medical team’s tour of duty in Camp Bastion, Afghanistan, to explore the role of institutional context as a contributing factor to psychological injury from war. We find that exposure to war and its consequences invokes sustained experiences of senselessness, futility, and surreality that are partially rooted in cultural expectations, professional role identity, and organizational protocol, and can threaten people’s existential grounding in this institutional context. We argue that what makes work at war traumatic for some and not others is likely affected by the specific context through which people filter, frame, and cope with their experience. A contextual understanding of psychological injury at war that is based in organizational research can thus form an important part of better addressing this grand challenge.